The relationship between stress and burnout on ching efficacy of Tamil primary school teachers in Port Dickson, Negeri Sembilan - Zhang, Ying; Kovalan, Suganeswary; Ratnam, Vanaja; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Due to the globalization challenges, the education system and its policy becomes more complex and this has a direct impact to the teaching profession. In nurturing children’s academic performance and social emotional, teachers all over the world faces high levels of work-related stress and burnout which in turn affects their self-efficacy at work. The main purpose of this study being conducted in a Tamil primary school was to investigate the relationships between stress, burnout and teaching efficacy among Tamil Primary School Teachers who were from Port Dickson District in the state of Negeri Sembilan. The study was conducted via quantitative research approaches executed through self-administered questionnaires. The participants of this research were selected from eight of Tamil Primary School teachers in Port Dickson district through purposive sampling technique. A total of 80 participants served as respondents. Instruments for this study were adapted from the National Union Teachers (NUT) questionnaire on teacher stress, the Maslach Burnout Inventory Educators Survey (MBI-ES) and Bandura’s Instrument Teacher Self-Efficacy Scale questionnaires. The researchers performed descriptive analyses and Pearson correlations in the data analysis process. The results show that there is no significant relationship between Teacher’s stress level and teaching efficacy among Tamil primary school teachers. On the other hand, the results found that there is a significant correlation between job burnout and teacher’s self-efficacy. More ever, the researchers identify the most crucial factor that lead to teachers stress and burnout in their profession.